A percepção ambiental dos moradores do entorno do Rio Ariri, Ananindeua/PA - FREITAS, Odilena de Jesus Moraes (Universidade Federal do Pará, 2020)
The community near the river in the district Ananindeua- Ariri /Pa. characterized by population growth which resulted in gradual process of deterioration of the river population. This study aimed to analyze the environmental awareness of people living around the river Ariri in Ananindeua, State of Pará, in order to point out the inter-relations man-environmental, the prospects, satisfactions, dissatisfaction and conduct evaluations of the subjects studied. To achieve this goal, the research unfolded exploratory-descriptive with a questionnaire with semi-open questions to 353 individuals. The results show that the uncontrolled growth caused environmental degradation of the river, and the waste produced by the local population constitutes the greatest threat to it’s preservation. This perception suggests an interrelationship between the basic conditions of health and environmental problems, which contributes to a lower quality of life the population surveyed.